Pengembangan Lembar Kegiatan Siswa (LKS) Dan Media Pembelajaran Inkuiri Berbasis Keterampilan Berpikir Kritis - Jayanti, Ida Bagus Rini; Suyidno, Suyidno; Hartini, Sri (Universitas Lambung Mangkurat, 2014)
LKS at schools still contained the materials and exercises without learning media have been caused the low ability of students in critical thinking skills. Therefore, carried out a research that aims to produce LKS and learning media of inquiry based on critical thinking skills of junior high school students on the subject of pressure effectively. The research spesific objectives are to describe the feasibility of LKS and learning media, critical thinking skills of students, and the response of students towards LKS and learning media. This research is ASSURE model development. The subjects were 30 students of class VIII-C SMP Negeri 1 Banjarmasin. The data were analyzed by descriptive quantitative and qualitative. Findings were obtained: (1) LKS which developed satisfied feasibility about approach content, presentation instruction, presentation of content, appropriateness of content, and performance of physic, (2) learning media which developed satisfied feasibility about benefits, presentation, and use of media props, (3) critical thinking skills of students categorized as good, (4) the studentsÂ response of interests and attitudes towards LKS categorized as good, (5) the students response of interests and attitudes towards learning media categorized as very good. Retrieved conclusion that LKS and learning media of inquiry based on critical thinking skills of students who produced effectively.Â